Land repossessions (tekoharã) in Mato Grosso do Sul and facing the logic of financialization of the territory - Souza, José Gilberto de; Mizusaki, Márcia Yukari (Universidade de São Paulo, 2022)
The work focuses its analysis on private property, on the agricultural and financial dynamics of the land in Mato Grosso do Sul, based on the premise that the State has been the main legitimizing agent of the process of appropriation of the lands of the original towns that compete with the forms of struggle for the recovery of their traditional territories. The work begins with a brief ethno-historical-geographic contextualization of the Kaiowá and Guaraní with respect to the constitution of private land ownership, and the incorporation of this fraction of space in the national State and how territorial determinations of this social conflict are analyzed, understanding them as the state and movement of the socio-spatial practices of the subjects in the consolidation of hegemony and resistance projects. It is concluded that in opposition to the form of value, the centrality of the territorial determinations of agribusiness, the resumption of land (tekoharã) is generated, which represents the confrontation, the resistance, of the native peoples to the genocidal project of the capital-State.

El trabajo centra su análisis en la propiedad privada, en la dinámica agrícola y financiera de la tierra en Mato Grosso do Sul, desde la premisa de que el Estado ha sido el principal agente legitimador del proceso de apropiación de las tierras de los pueblos originales que compiten con las formas de lucha por la recuperación de sus territorios tradicionales. El trabajo comienza con una breve contextualización etno-histórica-geográfica de los Kaiowá y Guaraní con respecto a la constitución de la propiedad privada de la tierra, y la incorporación de esta fracción de espacio en el Estado nacional y se analizan las principales determinaciones territoriales de este conflicto social, entendiéndolas como el estado y movimiento de las prácticas socioespaciales de los sujetos en la consolidación de proyectos de hegemonía y resistencia. Se concluye que en oposición a la forma valor, centralidad de las determinaciones territoriales de la agroindustria, se engendran las reanudaciones de tierras (tekoharã), que representan la confrontación, la resistencia, de los pueblos originarios al proyecto genocida del Estado-capital.
La reanudacíon de tierras (tekoharã) en Mato Grosso do Sul y la confrontación con la lógica de financiarización del territorio
Keywords: Financialization of the territory; Indigenous resistance; Retaken (tekoharã); Private land ownership; Kaiowá and Guarani